The Importance of Midwifery Services in Achieving Healthy Cities: A Review Article - Fatmazehra AKPINAR SELVASLI; Serap EJDER APAY (Asian Journal of Health Research, 2022)
Introduction: WHO has developed the Healthy Cities Project, based on how a city can be a healthy city. Effective delivery of midwifery services is very important in delivering healthy services to all segments of the society. In this study, we aimed to draw attention to the importance of effective provision of midwifery services in the way of being a healthy city. Methods: Data were collected using the literature review method. The keywords "healthy city", "women-friendly city", "child-friendly city", "midwifery", "sustainable development" and "urban health" were used for the search. Turkish and English articles obtained through PubMed, GoogleAcademic were analyzed and compiled in line with the scope. The review of the subject was carried out between June and July 2022. Results: Healthy societies and cities can be achieved by protecting children from all kinds of harm from prenatal period to adulthood, providing quality birth and postpartum services to mothers and making these services accessible. In order to reach a healthy society, midwifery care provided by midwives is very important to protect and improve the health of women, families and children, and especially to reduce health inequalities in the society. In order to be a healthy city, midwifery care services must be well organized. Conclusion: The Healthy Cities Project makes significant contributions to the formulation, implementation and evaluation of health policies in the city. Each of the Sustainable Development Goals and the concept of a healthy city are interrelated. It is important for cities to organize and expand midwifery services well in order to achieve their sustainable development goals.